2016
DOI: 10.1002/adfm.201603826
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Silk Fibroin Materials at Mesoscale

Abstract: Silk fibers spun by silkworms or spiders at ambient temperature display unique mechanical strength, excellent biocompatibility and optical transparency, which offer unconventional interfaces to soft and curved biological systems. In comparison with conventional materials, the performance of soft matter, i.e., animal silks, is mainly determined by the structure at the mesoscale. To further extend the applications, functionalization of silk materials becomes is required, and mesoscopic material assembly (MMA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 86 publications
0
49
0
Order By: Relevance
“…These roles of Ca ions hinder the formation of crystalline β‐sheets and results in high amount of amorphous random coil structures . Moreover, the amide‐A peak (3276 cm −1 ) of the Ca‐modified silk representing the N–H stretching groups of the silk film was redshifted to 3250 cm −1 because NH 2 and NH bonds are coordinated to CaN bonds which are replaced from hydrogen bond through chelate reaction . Additionally, the newly observed 3350 cm −1 peak representing the OH stretching group of water molecules showed that Ca ions can capture water molecules from the atmosphere …”
Section: Resultsmentioning
confidence: 99%
“…These roles of Ca ions hinder the formation of crystalline β‐sheets and results in high amount of amorphous random coil structures . Moreover, the amide‐A peak (3276 cm −1 ) of the Ca‐modified silk representing the N–H stretching groups of the silk film was redshifted to 3250 cm −1 because NH 2 and NH bonds are coordinated to CaN bonds which are replaced from hydrogen bond through chelate reaction . Additionally, the newly observed 3350 cm −1 peak representing the OH stretching group of water molecules showed that Ca ions can capture water molecules from the atmosphere …”
Section: Resultsmentioning
confidence: 99%
“…A downside of this approach was the limited stability of around 24 h. In this respect, the authors proposed to use a vapor barrier based on paraffin wax that further protects the hydrogel lenses achieving a stability of at least 150 h. In addition to the excellent features of SF as packaging system, its compatibility with fluorescent and phosphorescent compounds is also remarkable. The interested reader will find more information in the excellent reviews …”
Section: Ileds Oleds and Lecs Based On Biological Materialsmentioning
confidence: 99%
“…To achieve enhanced or specific performance from the textile sensors, particular functional materials are required. In this regard, we apply the strategy of mesofunctionalization to enhance the temperature‐ and pressure‐sensing materials as well as the temperature and pressure distributions with a position precision of 1 mm 2 . A facile way of coating functional materials on biocompatible silk fiber‐sheathed yarn for fabrication into intelligent textiles is used in this work.…”
Section: Introductionmentioning
confidence: 99%